Meta-analysis: Relationship between Antenatal Care Visits and Exclusive Breastfeeding - Aurina Firda Kusuma Wardani; Asrori Ibnu Utomo (Journal of Health Promotion and Behavior, 2022)
Background: Breastmilk is the main source of nutrition for babies who cannot eat solid food until they are 6 months old. Exclusive breastfeeding education can be given as long as pregnant women make antenatal care visits. The purpose of this study was to determine the relationship between antenatal care visits and exclusive breastfeeding.Subjects and Method: This study was a meta-analysis with the following PICO, population: mothers. Intervention: antenatal care visits. Comparison: no Antenatal Care visits. Result: Exclusive breastfeeding. The articles used in this study were obtained from three databases, namely Google Scholar, Pubmed, and Science Direct. Keywords to search for articles are “Antenatal Care Attendance” or “Antenatal Care Visit” or “Prenatal Care” and “Exclusive Breastfeeding” or “exclusively breastfed”. Included articles are full-text English with a cohort study design from 2010 to 2021 and report on adjusted Odds Ratio (aOR) in multivariate analysis. Article selection is done by using PRISMA flow diagram. Articles were analyzed using the Review Manager 5.3 application.Results: A total of 9 cross-sectional studies involving 19,716 mothers from Africa, Europe, and Asia were selected for systematic review and meta-analysis. The data collected showed that mothers who had antenatal care visits increased 1.50 times for exclusive breastfeeding compared to mothers who did not visit antenatal care (aOR = 1.50; 95% CI = 1.18 to 1.89); (p < 0.001).Conclusion: Antenatal care visits increase exclusive breastfeeding.Keywords: antenatal care, exclusive breastfeeding, meta-analisisCorrespondence:Aurina Firda Kusuma Wardani. Study Program of Public Health, Universitas Veteran Bangun Nusantara Sukoharjo.  Jl Letjen Sujono Humardani No 1 Jombor, Sukoharjo, Jawa Tengah, Indonesia. Email: firdakw@gmail.com. Mobile: +6282135012135Journal of Health Promotion and Behavior (2022), 07(01): 9-17 DOI: https://doi.org/10.26911/thejhpb.2021.07.01.02